Epidemiological profile of salivary gland lesions diagnosed in a higher education institution: an observational and retrospective study of 381 cases - Claudio Freire Sesenta Junior; Camila Camarini; Isadora Balan; Lilian Cristina Vessoni Iwaki; Mariliani Chicarelli da Silva; Elen de Souza Tolentino (Acta Scientiarum. Health Sciences, 2020)
The aim of this retrospective and observational study was to report the prevalence and characteristics of salivary gland lesions (SGL) in patients treated at the State University of Maringa, between 1995 and 2018. Data from medical records of patients with neoplastic and non-neoplastic SGL concerning to age, sex, ethnicity, anatomical location, microscopic diagnosis and treatment were collected. All SGL with diagnosis confirmed by microscopic examination were considered. Of the 3,127 biopsied lesions, 381 (12.1%) SGL were identified. Caucasian (71%) women (51%) aging from 11 to 20 years (33%) were more affected. 88.5% (n= 337) were non-neoplastic lesions, 7% (n= 27) benign neoplasms and 4.5% (n= 17) malignant neoplasms. Mucocele was the most prevalent lesion (n= 269%), followed by pleomorphic adenoma (n= 25%). Recognition and appropriate management of these lesions is essential, especially because malignant neoplastic lesions of the salivary glands can be very aggressive.